2012
DOI: 10.1073/pnas.1203193109
|View full text |Cite
|
Sign up to set email alerts
|

Toxic fibrillar oligomers of amyloid-β have cross-β structure

Abstract: Although amyloid fibers are found in neurodegenerative diseases, evidence points to soluble oligomers of amyloid-forming proteins as the cytotoxic species. Here, we establish that our preparation of toxic amyloid-β 1-42 (Abeta42) fibrillar oligomers (TABFOs) shares with mature amyloid fibrils the cross-β structure, in which adjacent β-sheets adhere by interpenetration of protein side chains. We study the structure and properties of TABFOs by powder X-ray diffraction, EM, circular dichroism, FTIR spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
273
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(305 citation statements)
references
References 53 publications
(86 reference statements)
19
273
4
2
Order By: Relevance
“…17 The possibility that oligomers of Ab could be formed outside the membrane, bind to the cell surface and then span the membrane for the formation of active channels has been proposed by Shafrir et al 31 Further computational studies of Ab aggregation with three-fold symmetry in the presence of lipid membranes may help to identify which of the amyloid peptide models are stable and remain sufficiently open for ion diffusion. Note that a similar pore with side chains of M 35 lining the inner surface was also observed by Stroud et al 15 in the toxic Ab42 fibrillar oligomer model.…”
Section: Alred Et Alsupporting
confidence: 78%
“…17 The possibility that oligomers of Ab could be formed outside the membrane, bind to the cell surface and then span the membrane for the formation of active channels has been proposed by Shafrir et al 31 Further computational studies of Ab aggregation with three-fold symmetry in the presence of lipid membranes may help to identify which of the amyloid peptide models are stable and remain sufficiently open for ion diffusion. Note that a similar pore with side chains of M 35 lining the inner surface was also observed by Stroud et al 15 in the toxic Ab42 fibrillar oligomer model.…”
Section: Alred Et Alsupporting
confidence: 78%
“…By using this method, we successfully decoupled the aggregation from the HDX process. Importantly, we extracted kinetic information on the Aβ 42 aggregation at 25°C, indicating that the middle region of the Aβ 42 peptide (i.e., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] was the "seeding" region in aggregation, followed by the C-terminus hydrophobic region (i.e., [36][37][38][39][40][41][42] and then the N-terminus hydrophilic region (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Finally, we showed that this approach allowed us to examine directly the factors that affect the oligomerization of Aβ 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of amyloid fibrils invoke X-ray crystallography (22)(23)(24), EM (19,25,26), and thioflavin T fluorescence (19,27), revealing the polypeptide's global behavior, whereas NMR studies provide residue-level information for the fibrils (28)(29)(30). Nevertheless, we know little about soluble Aβ aggregates owing to their intrinsically high heterogeneity.…”
mentioning
confidence: 99%
“…84 . In this scenario, it is clear that the collision between monomers and the critical nuclei is the non-spherical case, and in fact, no theoretical formula of the collision rate is available for such a complicated shape.…”
Section: Appendix B: Derivation Of K1mentioning
confidence: 99%